Serum arginase as breast cancer marker - Luboiński, Grzegorz; Szkop, Iwona; Kamińska, Janina; Porembska, Zofia (Contemporary Oncology/Współczesna Onkologia, 2001)
In 150 women admitted with breast pathology, serum arginase level and serum ASPAT, ALAT, LDH, GGTP, IL-6 and Ca 15,3 were analysed. Arginase was found to be a most sensitive and cheapest breast cancer marker. Evaluation of arginase for monitoring of disease and effectiveness of treatment needs further investigation.